2018
DOI: 10.1186/s11658-018-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt7b/β-catenin signaling pathway is involved in the protective action of calcitonin gene-related peptide on hyperoxia-induced lung injury in premature rats

Abstract: BackgroundCalcitonin gene-related peptide (CGRP) can protect against hyperoxia-induced lung injury, making the upregulation of CGRP a potential therapeutic approach for this type of injury. However, the effects of CGRP on the Wnt7b/β-catenin signaling pathway are unclear. In this study, we investigated the roles of CGRP and the Wnt7b/β-catenin signaling pathway in hyperoxia-induced lung injury.MethodsPremature Sprague Dawley (SD) rats were exposed to 21, 40, 60 and 95% oxygen for 3, 7 and 14 days. The animals’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…32 It has been previously reported that Wnt7B is highly expressed in developing airway epithelial cells and is required for normal lung mesenchymal cell proliferation as a mediator of epithelial-mesenchymal interactions; inactivation of Wnt7B leads to inhibition of epithelial proliferation and stromal cell and bronchial branching disorders. 33 These previous observations are in accord with the theory that Wnt7B mediates lung branching The ligands and receptors of BMP signaling are highly expressed in the distal airways, and previous studies in which BMP4 was shown to be overexpressed in lung endoderm suggested that this factor plays an important role in lung morphogenesis. 34,35 In addition, BMP4 does not signal epithelial cells to adopt a distal fate but may regulate the expansion of proximal epithelial cells in the lung.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…32 It has been previously reported that Wnt7B is highly expressed in developing airway epithelial cells and is required for normal lung mesenchymal cell proliferation as a mediator of epithelial-mesenchymal interactions; inactivation of Wnt7B leads to inhibition of epithelial proliferation and stromal cell and bronchial branching disorders. 33 These previous observations are in accord with the theory that Wnt7B mediates lung branching The ligands and receptors of BMP signaling are highly expressed in the distal airways, and previous studies in which BMP4 was shown to be overexpressed in lung endoderm suggested that this factor plays an important role in lung morphogenesis. 34,35 In addition, BMP4 does not signal epithelial cells to adopt a distal fate but may regulate the expansion of proximal epithelial cells in the lung.…”
Section: Discussionsupporting
confidence: 84%
“…In the normal human lung development process, Wnt7B was dramatically upregulated in the respiratory airways from 7 to 17 weeks (pseudoglandular stage) but was barely detectable at 21 weeks 32 . It has been previously reported that Wnt7B is highly expressed in developing airway epithelial cells and is required for normal lung mesenchymal cell proliferation as a mediator of epithelial‐mesenchymal interactions; inactivation of Wnt7B leads to inhibition of epithelial proliferation and stromal cell and bronchial branching disorders 33 . These previous observations are in accord with the theory that Wnt7B mediates lung branching morphogenesis through the epithelial‐mesenchymal transition signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Tapia-Rojas et al highlighted the importance of Wnt/β-catenin signaling dysfunction in the onset of Alzheimer’s disease and proposed that the loss of canonical Wnt signaling was a triggering factor of Alzheimer’s disease [23]. Recently, Wang et al reported that CGRP protected against hyperoxia-induced lung injury in premature rats through the Wnt7b/β-catenin signaling pathway [24]. We hypothesized if the neuroprotective role of CGRP might be correlated with the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] In another study, it was found that CGRP protected the rat lungs from hyperoxia‐induced oxidative damage throughWnt7b/β‐catenin signaling. [ 39 ] A study performed on human osteoblasts revealed the relation between CGRP and Wnt/β‐catenin signaling‐mediated cell apoptosis. It was found that β‐catenin levels increased in the first 60 min after CGRP administration to primary human osteoblast culture.…”
Section: Discussionmentioning
confidence: 99%